MORFOLOGI BENIH IKAN SIDAT (GLASS EEL) DARI MUARA SUNGAI CIMANDIRI, PELABUHAN RATU, JAWA BARAT - Sri Murtini; Ridwan Affandi; Hidayat Hidayat (LPPM Universitas Bina Insan, 2021)
Glass eel is a seed of eel fish including diadromus fish group, when it spawns into the deep sea, and migrates to river mouths for enlargement and growth. The initial phase of development starts from leptocephalus which is shaped like a leaf floating in the ocean and develops into a glass eel phase with a body shape resembling a stem, transparent and not yet pigmentation, will migrate anadromous to fresh waters through river mouths. It is feared that continuous catching of Glass eel will disturb this area, which can disrupt the living habitat of this seed. This study aims to determine the morphology of the glass eel fry. The method used in this study is field sampling using betel nets, and a description of the morphology of the glass eel presented in the data graph. Field observations obtained data on the length of the glass eel obtained ranging from 5-7 cm from the distribution of 3 different stations, stations 1 and 3 are locations where glass eel sizes are found in large numbers with body morphology that is still transparent and there is no color pigmentation on the body. The fertility level of the estuary waters affects the distribution of the glass eel.